2020
DOI: 10.3390/ijms21062110
|View full text |Cite
|
Sign up to set email alerts
|

Novel Physiology and Definition of Poor Ovarian Response; Clinical Recommendations

Abstract: Poor ovarian response (POR) to controlled ovarian stimulation (OS) presents a major challenge in assisted reproduction. The Bologna criteria represented the first serious attempt to set clear criteria for the definition of POR. However, the Bologna criteria were questioned because of the persistent heterogeneity among POR patients and the inability to provide management strategies. Based on these facts, a more recent classification, the POSEIDON (Patient-Oriented Strategies Encompassing IndividualizeD Oocyte N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 104 publications
0
23
0
Order By: Relevance
“…Poor ovarian response (POR) affects between 9% and 24% ( 1 , 2 ) of women undergoing assisted reproduction and is characterized by a failure to respond adequately to standard protocols and to recruit adequate follicles, resulting in reduced oocyte production and a diminished probability of pregnancy ( 3 ). POR is a therapeutic challenge that is amplified by a lack of consensus on the definition of POR and on the appropriate therapeutic approach for women with previous POR ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Poor ovarian response (POR) affects between 9% and 24% ( 1 , 2 ) of women undergoing assisted reproduction and is characterized by a failure to respond adequately to standard protocols and to recruit adequate follicles, resulting in reduced oocyte production and a diminished probability of pregnancy ( 3 ). POR is a therapeutic challenge that is amplified by a lack of consensus on the definition of POR and on the appropriate therapeutic approach for women with previous POR ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The threshold effect of female age showed that the inflection point was 34 years old, which means that when age is > 34 years old, the probability of live birth in POR patients drops sharply; when age ≤ 34 years of age, the probability of spontaneous miscarriage and female age were not significantly related. A large number of studies have shown that female age is very important in the quality of embryos and endometrial receptivity (10,23). With increasing age, the number and quality of oocytes are significantly reduced, the number of mitochondria and the ATP content in the cytoplasm significantly decrease, the proportion of abnormal embryo chromosome structure increases, and live birth is closely related to embryo chromosomal abnormalities (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…This distribution is different than the numbers reported in other studies and depends on the characteristics of the population seen at each center (Table 3). According to Abu-Musa, group 4 tends to be the group with the highest number of patients, accounting for about 55% of the patients, while group 3 amounts to about 10% (Abu-Musa et al, 2020). The study by Levi-Setti et al (2019) included IVF/ICSI patients in whom 1-9 oocytes had been retrieved, instead of selecting patients who had had ≤ 9 oocytes in a previous cycle of ovarian stimulation and aspiration, as described in the POSEIDON criteria.…”
Section: Discussionmentioning
confidence: 99%